A review of the possible applications of nanotechnology in refractory concrete - Antonovič, Valentin; Pundienė, Ina; Stonys, Rimvydas; Čėsnienė, Jūratė; Kerienė, Jadvyga (Journal of Civil Engineering and Management, 2010)
This article reviews the manufacturing nanotechnologies of modern refractory concretes and some other cementitious materials. The main part of the article focuses on the results obtained by the authors who analyzed the application of nanotechnology for manufacturing refractory concretes and examined the influence of nanostructure formation in the binding material on the properties of refractory concretes. In one case, investigations were carried out using two‐component (sodium silicate solution mixed with dicalcium silicate) and three‐component (sodium silicate solution mixed with dicalcium silicate plus calcium aluminate cement) binding materials, whereas in other case, multi‐component material, middle cement refractory concrete with mullite aggregates, microsilica and additives of single and hybrid deflocculant (polycarboxylate ether Castament FS20 and sodium tripolyphosphate) were researched. Preliminary investigations showed that the three‐component binding material under development hardens unlike the two‐component material as one of the binding components (combination of sodium silicate solution and dicalcium silicate) hardens very fast and affects the hydration process of the other component, calcium aluminate cement, which has a powerful impact on the whole structure of the already hardened material. The limited amount of water in the hardening structure provides conditions for the formation of the initial nanoclusters and nanolayers of amorphous hydrates. The application of nanotechnology in manufacturing refractory concretes has enabled to increase compressive strength 3 times – from 55 MPa to 165 MPa. First Published Online: 10 Feb 2011